ANALYSIS OF PRECISION MANUFACTURING PROCESSES THROUGH SIMULATION METHODS - N K, SACHIN; SHIVAKUMARA, B S; SRIDHAR, V (International Journal of Psychosocial Rehabilitation, 2020)
Modern technologies aid production systems have become easier than ever before. Simulation helps optimize the complications in the manufacturing processes. In this study, we are using Tecnomatix product life management software to identify the bottleneck, throughput, and buffer occupancy for the precision manufacturing process. Production line simulation has been done for the discrete interval time, i.e., the Poisson distribution (λ) and the log-normal distribution (σ, µ). CNC machines are used in the production line, and the same experiment was conducted to identify bottlenecks in the continuous production process and different buffer occupancy by detailed time study and process flow along the line. This paper helps to identify bottleneck operations and work in process status and proposes process changes to improve production efficiency. It helps in recognizing the status of buffer for present machine efficiency for throughput improvement using design experimentation.